Challenges in the Practice of Sexual Medicine in the Time of COVID-19 in the United Kingdom. Issue 7 (14th May 2020) - Jacob, Louis; Smith, Lee; Butler, Laurie; Barnett, Yvonne; Grabovac, Igor; McDermott, Daragh; Armstrong, Nicola; Yakkundi, Anita; Tully, Mark A.
Abstract: Background: On 23rd March 2020, the UK government released self-isolation/social distancing guidance to reduce the risk of transmission of SARS-CoV-2. The influence such guidance has on sexual activity is not known. Aim: To investigate levels and correlates of sexual activity during COVID-19 self-isolation/social distancing in a sample of the UK public. Methods: This paper presents preplanned interim analyses of data from a cross-sectional epidemiological study, administered through an online survey. Outcomes: Sexual activity was measured using the following question: "On average after self-isolating how many times have you engaged in sexual activity weekly?" Demographic and clinical data were collected, including sex, age, marital status, employment, annual household income, region, current smoking status, current alcohol consumption, number of chronic physical conditions, number of chronic psychiatric conditions, any physical symptom experienced during self-isolation, and number of days of self-isolation/social distancing. The association between several factors (independent variables) and sexual activity (dependent variable) was studied using a multivariable logistic regression model. Results: 868 individuals were included in this study. There were 63.1% of women, and 21.8% of adults who were aged between 25 and 34 years. During self-isolation/social distancing, 39.9% of the population reported engaging in sexual activity at least once per week. Variables significantly associated with sexual activity (dependent variable) were being male, a younger age, being married or in a domestic partnership, consuming alcohol, and a higher number of days of self-isolation/social distancing. Clinical Implications: In this sample of 868 UK adults self-isolating owing to the COVID-19 pandemic, the prevalence of sexual activity was lower than 40%. Those reporting particularly low levels of sexual activity included females, older adults, those not married, and those who abstain from alcohol consumption. Strength and Limitations: This is the first study to investigate sexual activity during the UK COVID-19 self-isolation/social distancing. Participants were asked to self-report their sexual activity potentially introducing self-reporting bias into the findings. Second, analyses were cross-sectional and thus it is not possible to determine trajectories of sexual activity during the current pandemic. Conclusion: Interventions to promote health and well-being during the COVID-19 pandemic should consider positive sexual health messages in mitigating the detrimental health consequences in relation to self-isolation/social distancing and should target those with the lowest levels of sexual activity.